Biodiversity monitoring in the environmental impact assessment of mining projects: a (persistent) waste of time and money? - Amanda Monique da Silva Dias (Perspectives in Ecology and Conservation, 2017)
Environmental impact assessments, not only in Brazil, but also globally, have long had their effectiveness questioned. Among the most frequently debated problems are: low quality of the impact assessment statements, weak public participation, project delays, increased costs for proponents, amongst others. The ineffectiveness of the environmental impact assessment system is corroborated by recent scholarly articles that argue that poor follow-up is one of the key elements behind the worst environmental disaster in Brazil, the Fundão Dam failure. The quality of monitoring programs has long been criticized in Brazil for being partially implemented and for failing to clearly translate into better environmental decision-making. This paper discusses the state of environmental impact assessment related to biodiversity monitoring programs in Brazil's mining regions, highlighting the political interference around this practice. Biodiversity monitoring programs should set a collection protocol, using a robust sampling design, with sufficient survey effort, spatial replication, methodological consistency and time to detect eventual ecological alterations. Without scientific rigor, collected data may have no value for decision-making, representing a complete waste of time and money.